Opportunities for English Language Learning of International Students in Malaysia. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2014)
Malaysia aspires to be the hub of education regionally (Kerr, 2011) and also internationally (Model for Success, 2008). Thus, Malaysia strives to recruit 200,000 international students (ISs henceforth) by year 2020 (Chi, 2011). The 2010 statistics indicate that there were 86,923 foreigners registered as ISs in public and private higher education institutions in Malaysia in 2010 (Ministry of Higher Education, 2010). Public universities, especially the five research universities – Universiti Malaya, Universiti Sains Malaysia, Universiti Kebangsaan Malaysia, Universiti Teknologi Malaysia, and Universiti Putra Malaysia have been enrolling more ISs in their establishment as this increases their world ranking (Tham & Kam, 2008). Having more ISs in the education landscape in Malaysia would mean that there is a need for a common language for interaction especially in the academic sector. In this case, English is the lingua franca as it is widely used as the “language of international communication and trade, science and technology, and as the vehicle for the acquisition of knowledge” (Zuraidah Mohd. Don, 2012:2). Although not an English-speaking country, Malaysia, like other receiving countries, puts emphasis on English as it is the language to be used in the academic milieu. Furthermore, Yusliza Mohd. Yusoff and Chelliah (2010) propose proficiency in the English language as one of the seven variables that can predict the adaptation level of ISs in Malaysia. Thus, reporting one part of the findings from a larger study, this article looks at opportunities in learning and using the English language reported by nine ISs studying at a public university in Malaysia.